EFFECT OF BRAND AMBASSADOR AND PRODUCT QUALITY ON PURCHASING DECISIONS WITH BRAND IMAGE AS AN INTERVENING VARIABLE (CASE STUDY ON SCARLETT WHITENING PRODUCT USERS IN MAKASSAR CITY) - Kala, Febriani; Sudirman, Indrianty; Razak Munir, Abdul (Scientia Integritas Utama, 2022)
This study aims to determine the effect of brand ambassadors and product quality on purchasing decisions with brand image as an intervening variable for users of Scarlett Whitening products in Makassar City. This research is a quantitative research, the data used is primary data obtained from distributing questionnaires to research objects. The population in this study are users of Scarlett Whitening products in Makassar City. The sampling technique used purposive sampling so that a sample of 385 respondents was obtained. The analytical method used in this study uses regression analysis through the PLS (Partial Least Square) method with the help of SmartPLS 3.0 Software. The results of the study show that (1) brand ambassadors have a positive and significant effect on Scarlett Whitening's brand image; (2) product quality has a positive and significant effect on Scarlett Whitening's brand image; (3) brand image has a positive and significant effect on purchasing decisions for users of Scarlett Whitening products in Makassar City; (4) brand ambassadors have a positive but not significant effect on purchasing decisions for users of Scarlett Whitening products in Makassar City; (5) product quality has a positive and significant effect on purchasing decisions for users of Scarlett Whitening products in Makassar City; (6) brand ambassadors have a positive and significant effect on purchasing decisions through brand image for users of Scarlett Whitening products in Makassar City